Localization of Virtual Sound Source Reproduced by the Crosstalk Cancellation System Under Different Reflective Conditions - TAN, Wei; YU, Guangzheng; ZHU, Jun; RAO, Dan (Archives of Acoustics, 2025)
This study explores the localization of virtual sound source reproduced by the crosstalk cancellation system under different reflective conditions in virtual rooms and analyzes the localization results with binaural cues. Binaural room impulse responses are generated using the high-order image source method. By modifying the acoustic parameters of the virtual room to manipulate the intensity and temporal structure of the reflection, psychoacoustic experiments were conducted using headphone reproduction. The experimental results indicate that, changes in reflection intensity within a certain range by altering the room reverberation time (RT) do not cause noticeable variations in virtual source localization. Increasing the loudspeaker–listener distance (changing temporal structure of reflections) deteriorates localization performance. The primary distinction between variations in the loudspeaker–listener distance and RT lies in whether the temporal structure of the reflection component changes. Overall, the study highlights the importance of the reflection temporal structure in the virtual source localization. The analysis of binaural cues indicates that, even in reverberant environments, the interaural time difference exhibits greater consistency with localization than the interaural level difference.